Time-optimal boundary control of a parabolic system with time lags given in integral form - Kowalewski, Adam; Krakowiak, Anna (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the time-optimal boundary control problem for a distributed parabolic system in which time lags appear in integral form in both the state equation and the boundary condition is presented. Some particular properties of optimal control are discussed.
Keywords: time-optimal boundary control; parabolic system; time lags